Depressive symptoms and self-esteem in burned individuals assisted in the center of reference (Research, Society and Development, 2020)
Objective: To evaluate the presence and intensity of depressive symptoms and self-esteem in burns. Methods: Quantitative, exploratory-descriptive study, with 36 participants from the Burns Treatment Center in Londrina / PR, between January 2016 and May 2019. Interviews conducted in two moments with the application of psychometrics scales for depression (Beck, Hamilton and Montgomery-Asberg), Rosenberg's self-esteem and semi-structured questionnaire. Data analysis using the Shapiro-Wilk, chi-square, Mann-Whitney and Student t tests, Spearman's correlation coefficient. Results: Most participants showed low self-esteem, worsening from the first to the second interview, with significance for income (p = 0.007), having a previous depressive diagnosis (p = 0.04), professing faith (p = 0.005). Most presented moderate and severe depressive symptoms, with an increase in intensity from the first to the second evaluation moment. Conclusion: the intensity of depressive symptoms increased and worsened self-esteem related to self-image caused by burns.